2008
DOI: 10.2140/ant.2008.2.573
|View full text |Cite
|
Sign up to set email alerts
|

Integral traces of singular values of weak Maass forms

Abstract: We define traces associated to a weakly holomorphic modular form f of arbitrary negative even integral weight and show that these traces appear as coefficients of certain weakly holomorphic forms of half-integral weight. If the coefficients of f are integral, then these traces are integral as well. We obtain a negative weight analogue of the classical Shintani lift and give an application to a generalization of the Shimura lift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 19 publications
2
56
0
Order By: Relevance
“…Remark. Note that these results generalize works of Duke and Jenkins [DJ08] and Miller and Pixton [MP10]. We also obtain the results in Section 9 of [Zag02] as a special case.…”
Section: Introduction and Statement Of Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Remark. Note that these results generalize works of Duke and Jenkins [DJ08] and Miller and Pixton [MP10]. We also obtain the results in Section 9 of [Zag02] as a special case.…”
Section: Introduction and Statement Of Resultssupporting
confidence: 83%
“…Zagier's results were generalized in various directions, mostly for modular curves of genus 0 [BO07,DJ08,Kim09,MP10]. Building upon previous work of Funke [Fun02] Bruinier and Funke [BF06] showed that Zagier's result on the traces of the j-function can be obtained as a special case of a theta lift using a kernel function constructed by Kudla and Millson [KM86].…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…We apply this to F (z) which is a weight −2 weakly holomorphic modular form, a meromorphic modular form whose poles are supported at cusps. Theorem 3.6 is a new result which adds to the extensive literature (for example, see [5,9,10,13,14,15,22,29,30]) inspired by Zagier's seminal paper [34] on "traces" of singular moduli.…”
mentioning
confidence: 99%
“…(3) As pointed out by the referee, in the absence of holomorphic cusp forms (k < 6), an obvious modification of the theorem (with f = 0 and arbitrary λ p ) remains true for k ≥ 2. This follows from (3.4) and was essentially proven by Duke and Jenkins [8].…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 53%
“…However, the authors [4] found an appropriate definition of J κ ⊆ S ! κ which makes use of so-called Zagier lifts [8,15], whose main properties where discovered by Duke and Jenkins [8].…”
Section: Introduction and Statement Of The Resultsmentioning
confidence: 99%